-10x + 48 = -6x+24
48 - 24 = -6x + 10x
24 = 4x
x = 24/4
x = 6
F(x) = x^2 - 6x + 4 {-3, 0, 5} (x, y) x is the domain, y is the range.
plug in the domain numbers into the equation to find the range.
y = x^2 - 6x + 4
y = -3^2 - 6(-3) + 4
y = 9 - (-18) + 4
y = 9 + 18 + 4
y = 31 (-3, 31)
y = x^2 - 6x + 4
y = 0^2 - 6(0) + 4
y = 0 - 0 + 4
y = 4 (0, 4)
y = x^2 - 6x + 4
y = 5^2 - 6(5) + 4
y = 25 - 30 + 4
y = -1 (5, -1)
c. {-1, 4, 31}
hope this helped, God bless!
Answer: (x+1)(x+2)
step by step explanation:
B because the sum of 2 sides must be GREATER than the 3rd side